The digital library as an enterprise: the Zachman approach - Abdullah, A.; Zainab, A.N. (2008)
The purpose of this paper is to examine the needs of digital library stakeholders and how a collaborative digital library might be designed to meet these needs. The collaborative digital library has been conceived to support secondary school students' information needs in conducting school-based projects. Design/methodology/approach - The paper uses the Zachman Framework for Enterprise Architecture as the approach to investigate the user requirements and define the digital library organization, resources, processes, technology and information flows In applying the Zachman Framework and to holistically control the study, the case study approach and multiple data collection techniques were adopted. Findings - Information obtained from these data gathering techniques helps to populate the requirements of the top three layers (18 cells) in the Zachman Framework to ascertain the design details of the digital library's scope, business and system model. The framework requires the abstraction of the characteristics and features of the digital library based on Zachman's six dimensions - motivation, data, people, process, place and time - as well as explains their structures and processes from the perspectives of the planner, owner and designer of the digital library. Originality/value - The paper is of significance in the field of collaborative digital libraries, since the perspectives and dimensions established from the framework comprehensively capture the user needs and context of use, and help ensure that everything relevant to the digital library enterprise is covered.